PENETAPAN WALI HAKIM SEBAGAI PENGGANTI WALI ‘ADAL DI KANTOR URUSAN AGAMA (KUA) KECAMATAN NOGOSARI KABUPATEN BOYOLALI - Nedy, Jon; Syamsuddin; baehaqi (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
The purpose of this study is to explain the issue in the case of the 'adl guardian that occurred in the Office of Religious Affairs (KUA) in Nogosari Subdistrict, where the guardian of the female prospective bride refused to marry his sister with the reason of not wanting to interfere in the marriage affairs of his sister.This study uses qualitative methods and research approaches in this study through interviews, observation, documentation studies. Interviews were conducted with the head of the Office of Religious Affairs at the KUA, Nogosari District. Observations were carried out in the area of ​​the KUA Religious affairs office, Nogosari District, Boyolali Regency. Documentation studies are taken from related research. The results of the study show that the process of determining a judge's guardian as a substitute for an ‘adal guardian is implemented at the KUA, Nogosari District, Boyolali Regency. The bride and groom submit a marriage proposal. The KUA examined the requirements put forward by the applicant, after examining the requirements it was found that the nasab guardian did not want to be the guardian of the applicant's marriage, then the KUA provided an alternative to the bride and groom to file a claim for guardian ‘adal to the Boyolali Religious Court, then the Boyolali Religious Court granted the applicant's request with a decision married the two prospective bride and groom, namely Warsinah Binti Joyo Sukarto with Suratno bin Sastro Semitro. Where acting as the judge's guardian is the head of the Nogosari District Office of Religious Affairs (KUA), namely Mr. M.Muslih, S.Ag., M.Ag., That the legal status of the judge's guardian as a substitute for the ‘adal guardian according to positive law and Islamic law is considered valid or permissible if the judge's decision is already there. Keywords: ‘adal guardian, judge guardian, Legal Status of the Guardian Judge